Agency of ecological landscapes through paintings of the American West - Hinkelman, Adam, author; Osborne, Erika, advisor; Lajarin-Encina, Aitor, advisor; Harrow, Del, committee member; Moore, Emily, committee member; Bowser, Gillian, committee member (Colorado State University. Libraries, 2024)
The lineage of American landscape paintings invokes a hierarchical structure cresting with humankind and the divine. This evokes problematic relational dynamics between humanity and the natural world which is exacerbated by Anthropocentric activity. Traditionally, early western landscape artists illustrated nature as a sublime force displayed as vast expanses of "untamed" wilderness, ethereal mountain peaks, fertile valleys, and steaming brooks. Alongside colonial settlements, paintings effectively lured eager European Americans to claim land through western expansion. To promote mutualistic bonds between humans and nature and contribute towards a new decolonial ecology, my thesis instills agency to natural landscapes by exploring a synthesis between generational historicity to place, non-anthropocentric phenomenology through kinship, and a painting process enriched by the practice of ultra distance trail running. More specifically, my paintings recognize the innate agency of trees, mountains, and glaciers through non-human centric perspectives across time scales, spatial dimensions, and non-observable light wave spectrums. This invites observers to identify a kinship with nature from non-anthropocentric grounding.
Keywords: geology; painting; landscape; ecology